Answer:
9/4
Step-by-step explanation:
First you must combine like terms, the two terms I this expression are x, and xy. So by adding -2xy to -2xy you get -4xy. Next you must add 3x to 3x. This gives you the simplified expression -4xy+6x. Hope this helps
Answer:
it depend
Step-by-step explanation:
hopefully i help
Answer:
16
Step-by-step explanation:
x+y=30 solve for x x=30-y
substitute x with 30-y and solve
11.25x+22.4y=515.9
11.25(30-y)+22.4y=515.9
337.5+11.15y=515.9
11.15y=178.4
y=16
since we're solving for just large candles it's 16
if need small cangle number 30-16=14
Answer:
-cos^4(x)
Step-by-step explanation:
Step 1: Use the Pythagorean identity : 1=cos^2(x) + sin^2(x)
1-sin^2(x) = cos^2(x)
-1+sin^2(x) = -cos^2(x)
cos^2(x) (-cos^2(x))
Step 2: Factor out common terms cos^2(x)
cos^2(x) (sin^2(x)-1)
Ans: -cos^4(x)